PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 005 BATU GAJAH - Helmawati '; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : This research is motivated by the fach that is found in the class IV SDN 005 Batu Gajah, which shows the results of learning in IPS is still relatively low. Formulation the problem is this research : “Does the application of cooporatife tipe Numbered Heads Together (NHT) model can improve learning outcomes IPS students of SDN 005 Batu Gajah with application of learning models cooporatife Numbered Heads Together (NHT). The hypothesis og this study is that if applied learning model Numbered Heads Together (NHT) it can improve learning outcomes in IPS student of SDN 005 Batu Gajah. This study was conducted in SDN 005 Batu Gajah in March and April 2016. This from is research is classroom action research ( PTK ) planned as much as two cycle.The subjects were student of class IV SDN 005 Batu Gajah academic year 2015/2016 which amount to 20 people consisting of 12 men and 9 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle 69,00 the second meeting of the first cycly of 84,75. Teacher activity observation sheet also increased at every meeting. At the first meeting of the first cycly of 50% and the second meeting of the first cycly of 76,19% . At the first meeting of the first cycly of 91,30% and of the second cycly of 95,83%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 58,33%, the second meeting of the first cycly of 75%, at the fourth meeting of the second cycle of 79,16%, and the fifth meeting of the second cycle of 91,66%. Mastery learning outcomes to repeat at first cycle increased 69,00 from the base score of 65,70. In the second cycle increased by 84,75. The average value in the base score 65,70, UH then the first cycle to 69,00 with an increase of 5,02%. Where as the second cycle of the average value of UH becomes 84,75 with an increase of 28,09%. So that research result are consistent with the hypothesis. Keywords : Numbered Heads Together (NHT) model of teaching, learning outcomes IPS